2015
DOI: 10.1371/journal.pone.0118195
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cell-Free mSHOX2 Plasma DNA for Therapy Monitoring in Advanced Stage Non-Small Cell (NSCLC) and Small-Cell Lung Cancer (SCLC) Patients

Abstract: PurposeMost patients suffering from advanced lung cancer die within a few months. To exploit new therapy regimens we need better methods for the assessment of a therapy response.Material and MethodsIn a pilot study we prospectively enrolled 36 patients with advanced NSCLC and SCLC (34 stage IV, 2 stage IIIB) of whom 34 received standard platinum-based chemo/radiotherapy and two were treated with a tyrosine kinase inhibitor. We measured the levels of extracellular methylated SHOX2 DNA (mSHOX2) in plasma before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 38 publications
5
49
2
Order By: Relevance
“…We assume that even extramedullary leukemic cells may provide nucleic acids that can be detected in the analysis of CRNA. Data from studies of solid tumors also support the concept that plasma/serum samples have a tendency to be enriched with tumor-specific CRNA [33][34][35]. This enrichment is perhaps due to the high turnover of the tumor cells, compared with nonmalignant cells.…”
Section: Discussionmentioning
confidence: 71%
“…We assume that even extramedullary leukemic cells may provide nucleic acids that can be detected in the analysis of CRNA. Data from studies of solid tumors also support the concept that plasma/serum samples have a tendency to be enriched with tumor-specific CRNA [33][34][35]. This enrichment is perhaps due to the high turnover of the tumor cells, compared with nonmalignant cells.…”
Section: Discussionmentioning
confidence: 71%
“…Wang and colleagues reported an elevated level of adenomatous polyposis coli (APC) and RASSF1A promoter methylation in ctDNA within 24 h after cisplatin-based therapy, consistent with chemotherapyinduced cell death (52). Methylation of SHOX2, RASSF1A and RARB2 has shown potential to monitor disease recurrence after surgery and chemotherapy (49,53). The value of methylated ctDNA to predict response to therapy has also been investigated.…”
Section: Methylated Ctdna In the Prediction And Monitoring Of Responsmentioning
confidence: 99%
“…release of tumor DNA from responding tumor cells. Accordingly, a proof-of-concept study showed that the longitudinal measurement of SHOX2 ccfDNA methylation allowed for the assessment of the response to cytotoxic treatment of patients with advanced lung cancers [22].…”
Section: Therapy Response Monitoringmentioning
confidence: 99%